Growth performance, survivability and profitability of improved smallholder chicken genetics in Nigeria: A COVID-19 intervention study - Bamidele, Oladeji; Akinsola, Oludayo Micheal; Yakubu, Abdulmojeed; Hassan, Waheed Akinola; Ogundu, Uduak Emmanuel; Amole, Tunde Adegoke (Frontiers in Genetics, 2023)
The impact of COVID-19 pandemic on smallholder farming households (SFH) includes increased poverty, and loss of livelihoods. Provision of livestock to SFH is a helpful intervention to mitigate this impact. This study provided a total of 150 smallholder poultry farmers, randomly selected from three states (Kebbi, Nasarawa and Imo) in Nigeria, with ten 5-week-old chickens (mixed sexes) each, of either FUNAAB Alpha or Noiler breed. The improved, dual-purpose hybrid chicken breeds were evaluated for growth performance (GP), survivability and profitability. The birds were managed under semi-scavenging production system. Body weight, mortality, and cost of production (COP) were recorded every four weeks until 21 weeks of age. Profitability was a function of the COP, and the selling price for live-birds (cocks). Body weight of Noiler (1927g) birds was not significantly (P>0.05) higher than FUNAAB Alpha (1792 g) at 21 weeks. Agroecology and breed had significant (P<0.05) effects on GP and survivability. Survivability of FUNAAB Alpha was higher (P<0.05) than Noiler, with Nasarawa (81-96%), having the highest (P<0.0001) survival rate compared to Imo (62-81%), and Kebbi (58-75%). At 21 weeks, the number of cocks and hens differed significantly (P<0.05) within the states (Imo: 2.4±0.2 and 5.4±0.3; Kebbi: 2.6±0.2 and 5.5±0.3; and Nasarawa: 2.9±0.2 and 5.8±0.3). Nasarawa (NGN 7,808; USD 19) ranked best for profitability, followed by Kebbi (NGN 6,545; USD 16 ) and Imo (NGN 5,875; USD 14). Overall, this study demonstrates that provision of improved chickens to vulnerable SFH in Nigeria holds great potential for economic growth, and resilience during emergencies, such as the COVID-19 pandemic.